2018
DOI: 10.26449/sssj.470
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reasons for Changes in Eating Behaviours of University Students

Abstract: The purpose of this study is to determine changes and reasons for eating behaviors of first-year university students after starting university. Using an eating behavior scale, we asessed the eating behavior before and after commencing university of 330 first year undergraduates who study in Ankara. 84.6% of the students who stated that they had changed their eating behaviors who live away from their family. It has been determined that the majority of the students who change their eating behaviors (77.6%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…31 Therefore, interventions should be made to enhance the healthy eating behavior of university students and to correct the factors that could develop unhealthier eating pattern among them. 31 Furthermore, as revealed by the current study there was a dramatic weight change among students after starting university, mostly decrease in body weight as reported by students. However, according to the BMI, the results of this study found that most of students had normal body weight.…”
Section: Discussionmentioning
confidence: 99%
“…31 Therefore, interventions should be made to enhance the healthy eating behavior of university students and to correct the factors that could develop unhealthier eating pattern among them. 31 Furthermore, as revealed by the current study there was a dramatic weight change among students after starting university, mostly decrease in body weight as reported by students. However, according to the BMI, the results of this study found that most of students had normal body weight.…”
Section: Discussionmentioning
confidence: 99%